The lactate to albumin ratio linked to all-cause mortality in critically ill patients with septic myocardial injury - Chen, Sheng; Guan, Senhong; Yan, Zhaohan; Ouyang, Fengshan; Li, Shuhuan; Liu, Lanyuan; Zhong, Jiankai (Frontiers in Cardiovascular Medicine, 2023)
The lactate to albumin ratio (LAR) has emerged as a promising prognostic marker in critically ill patients. Despite its potential utility, the prognostic value of LAR in septic myocardial injury (SMI) remains uncertain.Methods: This study aims to investigate the prognostic significance of LAR in SMI through a retrospective cohort analysis of data from the Medical Information Mart for Intensive Care III (MIMIC-III) (v1.4) database. The study included intensive care unit (ICU)-admitted patients (age ≥ 18 years) diagnosed with SMI. The primary endpoint was in-hospital mortality.Results: A total of 704 patients were included in the study, of which 59.10% were male. Hospital mortality and ICU mortality rates were recorded at 29.97% and 22.87%, respectively. After adjusting for confounding factors, multivariate Cox proportional risk analysis demonstrated that LAR was independently associated with an increased risk of both hospital mortality (HR, 1.39 [95% CI 1.24-1.56] P<0.001) and ICU mortality (HR,] P<0.001). Furthermore, the generalized additive model (GAM) and restricted cubic spline (RCS) model indicated a linear relationship between LAR and mortality rates in the ICU and hospital.The LAR may serve as a potential prognostic biomarker in critically ill patients with SMI. High LAR levels are associated with a higher risk of in-hospital mortality and can help identify individuals with high mortality rates. Overall, the findings emphasize the importance of using LAR as a tool for risk stratification and management of critically ill patients with SMI.